When Wall Street met Main Street : the quest for an investors' democracy - Ott, Julia C., 1974- (Harvard University Press, 2011)
The financial crisis of 2008 made Americans keenly aware of the impact Wall Street has on the economic well-being of the nation and its citizenry. Ott shows how the government, corporations, and financial institutions transformed stock investment from an elite to a mass practice at the beginning of the twentieth century.